2008
DOI: 10.1080/17482960801934239
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of plasma from Portuguese patients with familial amyotrophic lateral sclerosis

Abstract: In ALS, the identification of abnormal proteins in biological fluids might be useful for the understanding of the ethiopathogenesis of the disease. Furthermore, it can provide biomarkers useful for diagnosis, to monitor disease progression and to study the effect of drugs. Plasma is a suitable fluid for screening such targets since blood collection is a relatively simple procedure. In this study, proteomic techniques consisting of two-dimensional gel electrophoresis and matrix-assisted laser desorption time-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A number of proteomic screens have also attempted to identify novel players in the pathology of ALS (67), and to provide detectable biomarkers in biological fluids, such as plasma (68), cerebrospinal fluid, and brain extracellular fluid (69) of human patients. Transport defects are common to the various genetic etiologies in ALS (70), pointing to ALS as a spatiotemporal mislocalization disease, including mislocalization of mRNA (reviewed in (12)).…”
Section: Staufen1 Is Depleted From Msod1 Nmjs As Its Association Withmentioning
confidence: 99%
“…A number of proteomic screens have also attempted to identify novel players in the pathology of ALS (67), and to provide detectable biomarkers in biological fluids, such as plasma (68), cerebrospinal fluid, and brain extracellular fluid (69) of human patients. Transport defects are common to the various genetic etiologies in ALS (70), pointing to ALS as a spatiotemporal mislocalization disease, including mislocalization of mRNA (reviewed in (12)).…”
Section: Staufen1 Is Depleted From Msod1 Nmjs As Its Association Withmentioning
confidence: 99%
“…Gc2-2 individuals were overrepresented in sero-negative contacts of AIDS patients ( p  < 0.05).Pronk et al212 447 (96 AIDS patients and 351 homosexual men86NetherlandsCaucasian a Gc1F, Gc1S, Gc2NSPutkonen n et al218 125 (85 AIDS patients and 40 couples with 1 infected partner)3394SwedenCaucasian a Gc1F, Gc1S, Gc2NSRosberger et al227 1211011United StatesCaucasians and African AmericansGc1F, Gc1S, Gc2NSRheumatoid FeverBahr et al208 3990KuwaitArabicGc1F, Gc1S, Gc2An association was observed between Gc2 allele with rheumatic fever ( p  = 0.0024); 56% of all rheumatic fever patients were carriers of Gc2 allele.Tuberculosis (TB)Bahr et al208 4190KuwaitArabicGc1F, Gc1S, Gc2No association with GC alleles and TB, although an association was observed between Gc2 allele with rheumatic fever ( p  = 0.0024); 56% of all rheumatic fever patients were carriers of Gc2 allele.Martineau et al206 123 (United Kingdom); 130 (Brazil); 281 (South Africa)140 (United Kingdom); 78 (Brazil); 182 (South Africa)United KingdomVaried based on study location d Gc1F, Gc1S, Gc2Associations between GC polymorphism and TB only observed in Gujarati Asians from United Kingdom. Gc2-2 associated with susceptibility to active TB compared to wild type (Gc1-1): OR = 2.81 for Gc2-2 versus Gc1-1 (CI = 1.19–6.66, p  = 0.009) No associations were observed in the populations from Brazil and or South Africa. Neurodegeneration Amyotrophic Lateral Sclerosis (ALS)Palma et al182 11 (7 ALS, 4 other muscular disorders)…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the cytosolic superoxide dismutase ( SOD1 ) gene have been associated with ALS, but these account for less than 20% of all familial ALS (FALS)181. In Portuguese patients with FALS, proteomic analysis showed that the Gc-2 phenotype (436 K) was overrepresented in comparison to healthy controls182. The role of DBP in ALS is not known, but it is tempting to speculate that motor neuron damage resulting in the systemic release of actin and ensuing intravascular coagulation and local hypoxia-induced oxidative damage may be mitigated by the actin-scavenging properties of DBP.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical platform often used in ALS studies is based on 2D gel electrophoresis or liquid chromatography to separate proteins and matrixassisted laser desorption/ionization to generate ions in combination with mass analyzers, such as time-of-flight. [82] Kumar et al Transport of vitamin D sterols and actin-scavenging system [168] ↑: Higher metabolite levels in ALS patients compared with controls (i.e., ratio of metabolite levels in ALS:controls >1); ↓: Table 3 shows the chief proteomics studies in ALS. Cystatin C, a widely expressed cysteine protease inhibitor that is found in Bunina bodies on histopathological examination [86], is identified in most proteomics studies (Table 3) and in numerous targeted studies.…”
Section: Proteomicsmentioning
confidence: 99%